Modelling and differential costs evaluation of a two echelons repair system through infinite servers nodes queuing networks - Ferreira, Manuel Alberto M. (2013)
After a short report of results on infinite servers queues systems, focusing on its busy period, using networks of queues with infinite servers nodes a model is constructed to study a two echelons repair system. These repair systems may be useful, for instance, in the operation of a fleet of aircraft, of shipping or of trucks. Additionally it is shown how this model may be used in the evaluation of differential costs.